The Archaeology of Empires: A View from South Asia - Sinopoli, Carla M. (Bulletin of ASOR, 1995)
Archaeological and historic analyses of early empires has received considerable attention in recent years. This article examines major issues and challenges in the archaeology of empires and illustrates some of these with examples from the Vijayanagara empire of southern India. Four main challenges are identified: the vast scale of early empires, the broad internal variability that characterizes all archaic empires, the diverse and abundant sources of evidence that we must control, and the rapid pace of imperial development and collapse which often still exceeds the resolution of archaeological chronologies. The article calls for a comparative context from which to examine similarities and differences among imperial polities and their material manifestations.